A Novel Strategy for Determination of Paracetamol in the Presence of Morphine Using a Carbon Paste Electrode Modified with CdO Nanoparticles and Ionic Liquids. Issue 2 (29th July 2015) - Cheraghi, Somaye; Taher, Mohammad Ali; Karimi‐Maleh, Hassan
Abstract: A voltammetric sensor for determination of paracetamol in the presence of morphine is described for the first time. The synthesized CdO nanoparticles were characterized with different methods such as scanning electron microscopy (SEM) and X‐ray diffraction (XRD). The paracetamol and morphine peaks are separated ca. 0.37 and 0.65 V, respectively; hence paracetamol can be analysed in the presence of morphine and more than 21 times of the current excess of paracetamol. The detection limits for paracetamol and morphine were 0.07 and 0.1 μM, respectively. The sensor has been successfully applied for the assay of the above compounds in real samples. Abstract :